Muturu cattle breed management in the smallholder farming area of the Ouémé district in the south of Benin: rearing practices, objectives, and constraints - ADOLIGBE, Camus Mahougnon; AMAVEDA, M. A.; ADIDO, M. S; DJIMENOU, D.; FAROUGOU, SOUAÏBOU (My University, 2020)
An exploratory survey was conducted to understand breeding practices and breeding objectives as well as the constraints as a first step towards developing breeding strategies for the conservation of Muturu cattle breed in Ouémé smallholder farming area of South Benin. Data were generated through randomly interviewing 100 selected Muturu cattle keepers in the municipalities of Adjarra, Adjohoun, Akpro-Missérété, and Bonou using an electronic animal genetic resource characterization, inventory, and monitoring tool. Results indicated that the Muturu cattle were mainly kept for their meat. The mean herd sizes of 3, 5, 4, and 33 were obtained in Adjarra, Adjohoun, Akpro-Misserete, and Bonou respectively. Cattle keepers were exclusively male in the various municipalities surveyed except for Adjohoun, where 28.57% of cattle keepers were female. Preference was given to this breed because it is less demanding in terms of inputs and well adapted to the local environment. Mating was generally uncontrolled. The animals were fed on a natural pasture exclusively irrespective of the season. Robustness and vigor were the most frequently reported traits in selecting breeding bulls, while breeding females were kept based on their offspring’s growth and conformation. The decline in the number of Muturu cattle in the region was largely attributed to the competition for land used for other purposes such as crop cultivation and animal theft. Considering the devastating threat on the Muturu cattle breed, it is recommended that a participatory management scheme be designed and implemented for in situ conservation of the Muturu cattle breed in Benin.
Keywords: s Community-based breeding; Management; Indigenous; Sustainable use